Prospects and challenges for the Caribbean - Webb, Steven B. (World Bank WashingtonUS, 1997)
Looks at recent trends such as growth, growth prospects, and policy reform. Focuses on NAFTA and the Caribbean as well as on foreign capital and aid. Presents an agenda for action which highlights public sector reform, regulation, taxes, trade policy, labour and human resource development.